Ela, a criação: também em Clarice Lispector e Louise Bourgeois - Julia Gomes Panades (2017)
This study edges close to the theme of creation in the works of Clarice Lispector and Louise Bourgeois. Processual matters, composing gestures and figurations of birth are some of the variates on these thematic grounds. The manner in which creative experience figures in the body of such literary and plastic productions led this research to devoteitself not only to the study of the best known share of the works, but also to their peripheral lots, such as fragments, drafts, sketchnotes and testimonies that stage and put in doubt the theme of creation. The philosophy of Gilles Deleuze is the main line of conceptual articulation of this approach, which further aligns itself to sets of other texts (poetry, essays, criticism) that handle the theme of creation. The equation I do, I undo, I redo by Louise Bourgeois is a sort of chorus that conducts the ball of thread that unravels in this thesis.